2013
DOI: 10.1108/info-05-2013-0025
|View full text |Cite
|
Sign up to set email alerts
|

ICT access and usage among informal businesses in Africa

Abstract: Purpose – The purpose of this paper is to analyse the extent to which informal businesses employ information and communication technologies (ICTs) in their daily activities and the challenges they face in making use of ICTs. Design/methodology/approach – The study uses nationally representative data for informal businesses in residential and semi-residential areas, as defined by national census sample frames for nine African countries. Findings – The results show that mobile phones remain the most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…The India‐specific findings are not greatly different from other developing countries. A study (Deen‐Swarray, Moyo, & Stork, ) of more than 4000 informal enterprises spread across nine different African countries had shown that mobile phones are most used ICTs as compared with a minuscule use of landlines, computers, and the internet. Mobile interaction with suppliers is more than the interaction with customers.…”
Section: Use Of Icts and Impact On Informal Enterprises In Indiamentioning
confidence: 99%
“…The India‐specific findings are not greatly different from other developing countries. A study (Deen‐Swarray, Moyo, & Stork, ) of more than 4000 informal enterprises spread across nine different African countries had shown that mobile phones are most used ICTs as compared with a minuscule use of landlines, computers, and the internet. Mobile interaction with suppliers is more than the interaction with customers.…”
Section: Use Of Icts and Impact On Informal Enterprises In Indiamentioning
confidence: 99%
“…The rapid growth of ICT in the world has had the potentials of transforming the informal workers' sector by increasing growth, competitiveness and sustainability through better market access, cost reduction and wider business opportunities. Notwithstanding the fact that many technologies are available in the market, mobile phone has been a popular tool used by informal workers in Africa [10]. The choice of mobile phone is attributed by affordability, availability, lower costs, and wide access [10].…”
Section: B Technology Channelmentioning
confidence: 99%
“…The information and knowledge by ICT can develop rural community by facilitating through appropriate tools of communication. Deen-Swarray et al (2013) resulted from their study in Africa that ICTs may allow for a deepening of the distribution and procurement channels of business. Doing business over distance could become more affordable through the mobile phone and mobile money.…”
Section: An Overview Of the Literaturementioning
confidence: 99%